Carbon Nanoparticles in High‐Performance Perovskite Solar Cells. Issue 12 (17th January 2018) - Yavari, Mozhgan; Mazloum‐Ardakani, Mohammad; Gholipour, Somayeh; Marinova, Nevena; Delgado, Juan Luis; Turren‐Cruz, Silver‐Hamill; Domanski, Konrad; Taghavinia, Nima; Saliba, Michael; Grätzel, Michael; Hagfeldt, Anders; Tress, Wolfgang
Abstract: In the past few years, organic–inorganic metal halide ABX3 perovskites (A = Rb, Cs, methylammonium, formamidinium (FA); B = Pb, Sn; X = Cl, Br, I) have rapidly emerged as promising materials for photovoltaic applications. Tuning the film morphology by various deposition techniques and additives is crucial to achieve solar cells with high performance and long‐term stability. In this work, carbon nanoparticles (CNPs) containing functional groups are added to the perovskite precursor solution for fabrication of fluorine‐doped tin oxide/TiO2 /perovskite/spiro‐OMeTAD/gold devices. With the addition of CNPs, the perovskite films are thermally more stable, contain larger grains, and become more hydrophobic. NMR experiments provide strong evidence that the functional groups of the CNPs interact with FA cations already in the precursor solution. The fabricated solar cells show a power‐conversion efficiency of 18% and negligible hysteresis. Abstract : Carbon nanoparticles are incorporated in perovskite solar cells as a degradation inhibitor and perovskite crystal size magnifier. Here, carbon nanoparticles are used with functional groups in the perovskite solution, which interact with formamidinium cations resulting in morphology tuning, increased hydrophobicity, and thermal stability.